Potential of vibro-milling technique for preparation of electroceramic nanopowders - R. Wongmaneerung (2018)
The potential of the vibro-milling technique as a simple method to obtain usable quantities of single-phase electroceramic powders with nanosized particles was examined. A detailed study considering the role of both milling time and firing condition on phase formation and particle size of the final product was performed. The calcination temperature for the formation of the desired phase was lower when longer milling times have been applied. More importantly, by employing an appropriate choice of the milling time and calcination condition, high purity electroceramic nanopowders have been successfully prepared with a simple solid-state reaction method. © 2007 Elsevier Ltd and Techna Group S.r.l.